The action criminal bankruptcy - Larrea Simball, Leopoldo; Solórzano Soto, Rita Magdalena; Alvarado Moncada, Zoila (Revista Universidad de Guayaquil, 2018)
The problem of the extensive processing that establishes procedural legislation in civil matters in the case of shares with creditors to claim their rights, who finally decide to sue for criminal proceedings by the Arts was analyzed. 205 to 208 COIP, because in many cases, can not acquire the resources that belong to them, so it was proposed to analyze critically the prosecution in the process of bankruptcy, applying the qualitative method, deductive inductive, descriptive, bibliographic, field, with use of interview technique applied to the autoridade of the Faculty of Law of the University of Guayaquil, obtaining as most relevant finding that cases in which the bankruptcy must be vented under criminal law, is when fraudulent insolvency checks "and / or fraudulent bankruptcy by altering assets and liabilities, which is punishable by one to three years in prison, caused by the difficulty of the process of bankruptcy, because in the country is not what has been simplified so that it can guarantee the rights of creditors, increasing the risk of fraudulent action on insolvency, concluding checking the premise that criminal proceedings where fraudulent insolvency, must protect legal rights of creditors prior contest, suggesting a procedure for implementation of the precautionary measures under sum presumption of ownership of creditors against the persons involved in fraudulent insolvency.